(untitled) (Swiss Medical Weekly, 2025)
In this article, we describe and analyse when and what patients need to be told about the use of artificial intelligence in clinical care. In many circumstances, patients do not need to be told about the use of AI, but in cases in which AI is making decisions rather than supporting them or patient data are being transferred to a third party, specific consent must be sought from patients. Ultimately, AI will become a routine part of clinical care, but until then, clinicians must take great care to seek consent where necessary.